2006
DOI: 10.1007/s00428-006-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal rhabdomyoma: case report and review of the literature

Abstract: Rhabdomyomas are benign tumors in which at least some cells are differentiated as skeletal muscle cells with cytoplasmic cross-striations. Extracardiac adult rhabdomyoma is an extremely uncommon benign neoplasm that usually involves the head and neck region. Rare cases have been reported to involve other sites of the body including mediastinum. We report the fourth case of mediastinal adult rhabdomyoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Five cases of extra-cardiac non-syndromic rhabdomyoma have been described in the mediastinum. All patients were elderly adults (range 52–80 years; four males, one female) [ 21 , 101 , 126 , 182 , 233 ]. Symptomatic cases presented with non-specific signs.…”
Section: Skeletal Muscle Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Five cases of extra-cardiac non-syndromic rhabdomyoma have been described in the mediastinum. All patients were elderly adults (range 52–80 years; four males, one female) [ 21 , 101 , 126 , 182 , 233 ]. Symptomatic cases presented with non-specific signs.…”
Section: Skeletal Muscle Tumoursmentioning
confidence: 99%
“…Symptomatic cases presented with non-specific signs. All cases had at some connection with the cervical area, one case was multifocal with a second cervical tumour [ 233 ]. It has been suggested that rhabdomyoma may originate from the third and fourth branchial pouches or from myoid cells in the thymus [ 182 ].…”
Section: Skeletal Muscle Tumoursmentioning
confidence: 99%
“…There are two main types, cardiac and extracardiac, with extracardiac consisting of three clinical and histologic subtypes: adult, fetal and genital accounting for 50, 40, and 10% of tumors respectively. [3] Fetal RM are benign tumor with skeletal muscle differentiation mostly occur in head and neck region. It is observed in higher incidence in male children these includes newborn infant or very young children.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Fetal RM have variable cellularity with differing degrees of striated muscle differentiation and have a range of cell types. [3] They rarely show areas of necrosis, nuclear atypia and lack hypercellularity, abnormsally distributed chromatin and absent or low mitotic figure. [12] Desmin is the most reliable immunohistochemical marker for cells with skeletal or smooth muscle differentiation.…”
Section: Discussionmentioning
confidence: 99%